A Two‐Resonance Tapping Cavity for an Optimal Light Trapping in Thin‐Film Solar Cells. Issue 18 (18th May 2017) - Liu, Quan; Romero‐Gomez, Pablo; Mantilla‐Perez, Paola; Colodrero, Silvia; Toudert, Johann; Martorell, Jordi
Abstract : An optimal photon absorption in thin film photovoltaic technologies can only be reached by effectively trapping the light in the absorber layer provided a considerable portion of the photons is rejected or scattered out of such layer. Here, a new optical cavity is proposed that can be made to have a resonant character at two different nonharmonic frequencies when adjusting the materials or geometry configurations of the partially transmitting cavity layers. Specific configurations are found where a reminiscence of such two fundamental resonances coexists leading to a broadband light trapping. When a PTB7‐Th:PC71 BM organic cell is integrated within such cavity, a power conversion efficiency of 11.1% is measured. This study also demonstrates that when materials alternative to organics are used in the photoactive cell layer, a similar cavity can be implemented to also obtain the largest light absorption possible. Indeed, when it is applied to perovskite cells, an external quantum efficiency is predicted that closely matches its corresponding internal one for a broad wavelength range. Abstract : A two‐resonance tapping cavity is proposed for an effective broadband light trapping in the absorber layer of thin‐film solar cells. When this new optical cavity is applied to high performance polymer cells, an optimal light harvesting enhancement is achieved, corresponding to a 19% increase in power conversion efficiency.